Epigenetic Up-regulation of Large-Conductance Ca(2+)-Activated K(+) Channel Expression in Uterine Vascular Adaptation to Pregnancy - Chen, Man (2014)
Our previous study demonstrated that pregnancy increased large-conductance Ca(2+)-activated potassium (BK(Ca)) channel β1 subunit (BKβ1) expression and BK(Ca) channel activity in uterine arteries, which was abrogated by chronic hypoxia. The present study tested the hypothesis that promoter methylation/demethylation is a key mechanism in epigenetic reprogramming of BKβ1 expression patterns in uterine arteries. Ovine BKβ1 promoter of 2315 bp spanning from −2211 to +104 of the transcription start site was cloned and a Sp1(-380) binding site that contains CpG dinucleotide in its core binding sequences was identified. Site-directed deletion of the Sp1 site significantly decreased the BKβ1 promoter activity. Estrogen receptor-α bound to the Sp1 site through “tethering” to Sp1, and up-regulated the expression of BKβ1. The Sp1 binding site at BKβ1 promoter was highly methylated in uterine arteries of nonpregnant sheep, and methylation inhibited transcription factor binding and BKβ1 promoter activity. Pregnancy caused a significant decrease in CpG methylation at the Sp1 binding site and increased Sp1 binding to the BKβ1 promoter and BKβ1 mRNA abundance. Chronic hypoxia during gestation abrogated this pregnancy-induced demethylation and up-regulation of BKβ1 expression. The results provide evidence of a novel mechanism of promoter demethylation in pregnancy-induced reprogramming of BK(Ca) channel expression and function in uterine arteries, and suggest new insights of epigenetic mechanisms linking gestational hypoxia to aberrant uteroplacental circulation and increased risk of preeclampsia.